1998
DOI: 10.1097/00003226-199809000-00006
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of Fuchsʼ Endothelial Dystrophy

Abstract: In vivo confocal microscopic findings of Fuchs' endothelial dystrophy are described for the first time in a series of cases. Pathological changes in Fuchs' dystrophy were detected in all corneal layers, more frequently in the posterior layers. Endothelial cell counts obtained with confocal microscopy were statistically similar to those obtained with standard specular microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 0 publications
5
72
0
4
Order By: Relevance
“…18 Recently, the introduction of IVCM has enabled microscopical studies of the cornea in patients with FECD, [11][12][13]19,20 although to date, only few IVCM studies have investigated corneal changes in these patients. [11][12][13] To our knowledge, this study is the first to systematically and quantitatively analyze subbasal corneal nerve alterations in patients with early stage FECD by IVCM. Further, this is the largest study to date analyzing stromal and epithelial cell layers by IVCM in FECD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Recently, the introduction of IVCM has enabled microscopical studies of the cornea in patients with FECD, [11][12][13]19,20 although to date, only few IVCM studies have investigated corneal changes in these patients. [11][12][13] To our knowledge, this study is the first to systematically and quantitatively analyze subbasal corneal nerve alterations in patients with early stage FECD by IVCM. Further, this is the largest study to date analyzing stromal and epithelial cell layers by IVCM in FECD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Several prior studies have reported IVCM results in patients with FECD. [11][12][13] Chiou et al showed morphological alterations of corneal endothelium in FECD patients by tandem scanning IVCM, whereas Mustonen et al demonstrated pathological alterations in all corneal layers using slit scanning IVCM. In addition, Hara et al showed a significant correlation between the ECD as acquired by IVCM and non-contact specular microscopy in FECD patients.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Korneal konfokal mikroskopi ile hesaplanan endotel hücre dansitesinin speküler mikroskopi sonuçlarına benzer olduğu bildirilmiştir. 25 Hollingsworth ve ark., yaş ortalaması 41 yıl olan sağ-lıklı olgu grubunda ortalama endotel hücre dansitesini 3061±382 hücre/mm 2 olarak bildirirken, Niederer ve ark., yaş ortalaması 37,8 yıl olan Korneanın tüm dokular arasında en yoğun innervasyona sahip olduğu ve deriden 300-400 kat fazla sinir lifi içerdiği gösterilmiştir. 26 Korneal konfokal mikroskopi sayesinde korneal sinir lifleri non-invaziv olarak doğrudan görüntülenebilmekte, ve geliştirilen bilgisayar programları ile sinir lifi dansitesi, sinir lifi uzunluğu, sinir dalı dansitesi gibi parametrelere ulaşılabilmektedir.…”
Section: Discussionunclassified
“…2 Ancak çalışmalar guttata tespit edilmeden önce endotelde değişiklikler ve desme membranında kalınlaşma oluşabileceğini göstermiştir. 3 Guttata genellikle hasta halen asemptomatik iken beşinci ve altıncı on yıl civarında başlar. Hastalık yavaş ilerler, hastalar genellikle birlikte izlenebilen kataraktın gelişimesiyle beraber görme keskinliğinde azalma ile başvururlar.…”
Section: Introductionunclassified
“…Speküler mikroskopi, FED'ni tespit etmek için kolay ve güvenilir bir yöntemdir. [1][2][3] FED'de endotel hücreleri, normal olmayan görünüm ve sayıyla birlikte sağlıksızdır, katarakt ameliyatı sırasında hasara eğilimlidir ve sonuçta endotel yetmezliğe gidebilir. 4 Sonuç olarak, katarakt ameliyatı FED'nin seyrini hızlandırabilir ve bizim hastamızda olduğu gibi çoğu hasta katarakt ameliyatı sonrasında semptomatik hale gelir.…”
Section: Introductionunclassified